Different Gestational Diabetes Phenotypes: Which Insulin Regimen Fits Better? - Mecacci, Federico; Lisi, Federica; Vannuccini, Silvia; Ottanelli, Serena; Rambaldi, Marianna Pina; Serena, Caterina; Simeone, Serena; Petraglia, Felice (Frontiers in Endocrinology, 2021)
Objective Maternal characteristics and OGTT values of pregnancies complicated by gestational diabetes mellitus (GDM) were evaluated according to treatment strategies. The goal was to identify different maternal phenotypes in order to predict the appropriate treatment strategy. Methods We conducted a retrospective study among 1,974 pregnant women followed up for GDM in a tertiary referral hospital for high-risk pregnancies (Careggi University Hospital, Florence, Italy) from 2013 to 2018. We compared nutritional therapy (NT) alone (n = 962) versus NT and insulin analogues (n = 1,012) group. Then, we focused on different insulin analogues groups: long acting (D), rapid acting (R), both D and R. We compared maternal characteristics of the three groups, detecting which factors may predict the use of rapid or long-acting insulin analogue alone versus combined therapy. Results Among women included in the analysis, 51.3% of them needed insulin therapy for glycemic control: 61.8% D, 28.3% combined D and R, and 9.9% R alone. Age >35 years, pre-pregnancy BMI >30, family history of diabetes, previous GDM, altered fasting plasma glucose (FPG), hypothyroidism, and assisted reproductive technologies (ART) were identified as maternal variables significantly associated with the need of insulin therapy. Altered 1-h and 2-h glucose plasma glucose level at OGTT, age >35 years, and previous GDM were found as independent predicting factors for the use of combined therapy with rapid and long acting analogues for glycemic control. On the contrary, pre-pregnancy BMI <25 and normal fasting plasma glucose values at OGTT were found to be significantly associated to the use of rapid insulin analogue only. Conclusion A number of maternal and metabolic variables may be identified at the diagnosis of GDM, in order to identify different GDM phenotypes requiring a personalized treatment for glycemic control.